Rancang Bangun Aplikasi Berbasis Android dalam Mengembangkan UMKM Lapangan Futsal di Kota Medan - Fidelis Elinus Zebua; Arjon Samuel Sitio; Taufik Ismail Simajuntak (Riau Jurnal Teknik Informatika, 2026)
The development of futsal field Micro, Small, and Medium Enterprises (MSMEs) in Medan City faces obstacles in terms of disseminating field rental information to the wider community. Field owners struggle to promote their services, while customers often experience difficulties finding information about available fields and must visit locations directly. This research aims to produce an Android-based application that connects futsal field owners with customers to facilitate the information and field rental process in Medan City. The research methods used include data collection through literature study, observation, and field surveys. The research results show that the application can function properly based on black box testing of all features. The application successfully facilitates field owners in providing digital field rental information and makes it easier for customers to search for and rent futsal fields without having to come directly to the location. This application is expected to support the development of MSMEs in the sports sector, particularly futsal fields in Medan City.